(untitled) (Journal of Hama University, 2020)
The aim of this experiment was to study the effect of honey, ginseng and vitamin E on blood parameters after peritoneal injection of doxorubicin and cisplatin in hamster, and determine the protective effect of these substances on these parameters. The experiment was conducted on 108 adult hamsters, ranging in age from 3.5 to 4 months, and in weight from 60 to70 grams.The experimental animals were divided into 9 groups (12 animals in each group): G1 (control), G2 (Injected anticancer without oral administration), G3 (Injected anticancer + honey orally), G4 (Injected anticancer + vitamin E orally), G5 (Injected anticancer + ginseng orally), G6 (Injected with anticancer + honey and vitamin E orally), G7 (Injected anticancer + honey and ginseng orally), G8 (Injected anticancer + ginseng and vitamin E orally), G9 (Injected anticancer + honey, ginseng and vitamin E orally). The experiment lasted for 6 weeks, after peritoneal injection of anticancer agents, blood samples were taken from the lateral venous plexus of eye at the end of week 6, and blood parameters were measured: Hemoglobin concentration, Hematocrit, Red Blood Cells (RBCs), White Blood Cells (WBCs), and Platelets (PLT). It was found that peritoneal injections with anti-cancer negatively affected all blood parameters, and led to their reduction, while oral administration of protective substances led to reduce the decrease of blood standards and improve the blood image in experiment animals.